THE RELATIONSHIP BETWEEN NUMERICAL ABILITY, STUDENTS LEARNING INTEREST, AND ATTENTION OF PARENTS WITH MATH STUDENTS LEARNING OUTCOMES - Maulida Dharmawanti; Uswatun Khasanah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Results of low mathematics associated with many factors. Numerical ability, students learning interest, and attention of parents are several factors that allegedly associated with students’ mathematics learning outcomes. This research has to determine whether or not a positive and significant relationship between Numerical Ability, Students Learning Interest, and Attention of Parents with Math Students Learning Outcomes in Even Semester of an eighth-grade student SMP Negeri 1 Batur Banjarnegara Academic Year of 2015/2016. The population in this research were all student of class VIII in even semester in SMP Negeri 1 Batur academic year 2015/2016 with the total number of 82 students in 4 class. Function random sampling technique to class to take a sample class, as a sample class was class VIII D. Data collection techniques done with test method and the questionnaire method. The instruments test used the test of validity, different power, and reliability testing. Test requirements analysis used normality test, independent, and the linearity test. Analysis of data used linear regression analysis and correlation analysis. The results showed that there was a positive and significant relationship between the ability of numerical, students learning interest, and attention of parents with math learning outcomes with  and , in order to obtain  . Multiple correlation coefficient (R)  with a learn regression equation  . The relative contribution of (X1) , (X2) , and (X3)  with a coefficient of determination and effective contribution  (X1) , (X2) , and (X3) .